Cross sectional study of conventional cervical smear, monolayer cytology, and human papillomavirus DNA testing for cervical cancer screening - Coste, Joël (BMJ Publishing Group Ltd, 2003)
OBJECTIVES: To compare the sensitivity, specificity, and interobserver reliability of conventional cervical smear tests, monolayer cytology, and human papillomavirus testing for screening for cervical cancer. DESIGN: Cross sectional study in which the three techniques were performed simultaneously with a reference standard (colposcopy and histology). SETTING: Public university and private practices in France, with complete independence from the suppliers. PARTICIPANTS: 828 women referred for colposcopy because of previously detected cytological abnormalities and 1757 women attending for routine smears. MAIN OUTCOME MEASURES: Clinical readings and optimised interpretation (two blind readings followed, if necessary, by consensus). Sensitivity, specificity, and weighted κ computed for various thresholds of abnormalities. RESULTS: Conventional cervical smear tests were more often satisfactory (91% v 87%) according to the Bethesda system, more reliable (weighted κ 0.70 v 0.57), and had consistently better sensitivity and specificity than monolayer cytology. These findings applied to clinical readings and optimised interpretations, low and high grade lesions, and populations with low and high incidence of abnormalities. Human papillomavirus testing associated with monolayer cytology, whether systematic or for atypical cells of undetermined significance, performed no better than conventional smear tests. CONCLUSIONS: Monolayer cytology is less reliable and more likely to give false positive and false negative results than conventional cervical smear tests for screening for cervical cancer.